Retificador boost monofásico PWM de cinco níveis com correção do fator de potência - Kohler, Michel Andrey Freitas de Souza (2020)
The scope of this work is focused on a new topology for a multi-level single phase PWM rectifier AC-DC boost with power factor correction (PFC). The converter is characterized as unidirectional, low volume of inductors, high power factor, low THD, low voltage stresses, and number of components reduced. Will be analyzed the operating principles of this topology, mathematical analysis simulation and experimental results. For the latter, a 1 kW prototype will be built and tested, where the attained results will certify the feasibility of the proposed structure.